Die onderrig van verpleegbestuur - A.W. Beekman; S. Visser (AOSIS, 1983)
Nursing management today is a very complex function and there appear to be shortcomings in the teaching of the subject to student nurses. The authors suggest that teachers should use the problem solving process, which stimulates critical thinking and the application of principles by students. They also suggest simulation strategies such as role play, the in-basket technique, critical incidents and games to teach management skills.